2022
DOI: 10.1242/jcs.259280
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional tonicity-regulated nuclear trafficking of NFAT5 mediated by KPNB1, XPOT and RUVBL2

Abstract: NFAT5 is the only known mammalian tonicity-responsive transcription factor with essential role in cellular adaptation to hypertonic stress. It is also implicated in diverse physiological and pathological processes. NFAT5 activity is tightly regulated by extracellular tonicity, but the underlying mechanisms remain elusive. We demonstrated that NFAT5 enters the nucleus via the nuclear pore complex. We found that NFAT5 utilizes a unique nuclear localization signal (NFAT5-NLS) for nuclear import. siRNA screening r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that IMB1, a nuclear transport receptor, is required for NFAT5 nucleus translocation 18 . Co-IP confirmed that NFAT5 interacted with IMB1 in U251 and U87/EGFR cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that IMB1, a nuclear transport receptor, is required for NFAT5 nucleus translocation 18 . Co-IP confirmed that NFAT5 interacted with IMB1 in U251 and U87/EGFR cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tonicity-responsive enhancer binding protein (NFAT5, TonEBP), activated by hypertonicity, is initially identified as a central transcriptional regulator of osmoprotective response and the immune response 16 , 17 . Tonicity-regulated NFAT5 nuclear import depends on binding to the importin β1 (IMB1) 18 . Recent studies indicate that NFAT5 is overexpressed and associated with poor prognosis in GBM, pancreatic cancer, and melanoma 19 21 .…”
Section: Introductionmentioning
confidence: 99%